The frequency and clinical implication of mismatch repair protein deficiency in Chinese patients with ovarian clear cell carcinoma - Shuang Ye; Shuling Zhou; Siyuan Zhong; Boer Shan; Wenhua Jiang; Wentao Yang; Xu Cai; Huijuan Yang (BMC Cancer, 2022)
Abstract Background The aim of the present study was to assess the prevalence of deficient mismatch repair (MMR) in Chinese ovarian clear cell carcinoma (CCC) patients and its association with clinicopathologic features. Methods Immunohistochemistry with four antibodies against MLH1, PMS2, MSH2 and MSH6 was performed on whole section slides, and the results were correlated with clinicopathologic variables. Results A total of 108 cases were included in the present study with a median age of 52 years at first diagnosis. Early-stage disease and platinum-sensitive recurrence accounted for 62.3 and 69.6%, respectively, of the total cases. Overall, the estimated 5-year overall survival was 70.3 and 20.7% in patients with early- and late-stage tumors, respectively. Deficient MMR was identified in 5.6% (6/108) of the cohort and included MSH2/MSH6 (n = 4) and MLH1/PMS2 (n = 2). The average age of the six patients with deficient MMR was 45.6 years, and the rate of MMR-deficient tumors in women ≤50 years was relatively higher than that in women over 50 years (10.0% vs. 2.9%; P = 0.266). Half of the patients with deficient MMR were diagnosed with synchronous (endometrial or colorectal) and metachronous (endometrial) cancer, which was significantly more than their intact counterparts (P = 0.002). All six patients with deficient MMR had early-stage tumors, and the majority (83.3%) were platinum sensitive. The median progression-free survival was slightly higher in patients with defective MMR expression than in their intact counterparts (30 months vs. 27 months), but significance was not achieved (P = 0.471). Conclusions Young ovarian CCC patients with concurrent diagnosis of endometrial and colorectal cancer are more likely to have MMR-deficient tumors, thereby warranting additional studies to determine whether patients harboring MMR abnormalities have a favorable prognosis.